Seismic Evaluation and Retrofitting of an Existing Buildings-State of the Art - Abass, Haider Ali; Jarallah, Husain Khalaf (Al-Nahrain Journal for Engineering Sciences, 2021)
In this study, previous researches were reviewed in relation to the seismic evaluation and retrofitting of an existing building. In recent years, a considerable number of researches has been undertaken to determine the performance of buildings during the seismic events. Performance based seismic design is a modern approach to earthquake resistant design of reinforcement concrete buildings. Performance based design of building structures requires rigorous non-linear static analysis. In general, nonlinear static analysis or pushover analysis was conducted as an efficient instrument for performance-based design. Pushover analysis came into practice after 1970 year. During the seismic event, a nonlinear static analysis or pushover analysis is used to analyze building under gravity loads and monotonically increasing lateral forces. These building were evaluated until a target displacement reached. Pushover analysis provides a better understanding of buildings seismic performance, also it traces the progression of damage and failure of structural components of buildings.